Evaluation of shear bond strength of two resin-based composites and glass ionomer cement to pure tricalcium silicate-based cement (Biodentine®) - Kenan CANTEK?N; Serap AVC? (University of São Paulo, 2014)
Objectives: Tricalcium silicate is the major constituent phase in mineral trioxide aggregate (MTA). It is thus postulated that pure tricalcium silicate can replace the Portland cement component of MTA. The aim of this study was to evaluate bond strength of methacrylate-based (MB) composites, silorane-based (SB) composites, and glass ionomer cement (GIC) to Biodentine® and mineral trioxide aggregate (MTA). Material and Methods: Acrylic blocks (n=90, 2 mm high, 5 mm diameter central hole) were prepared. In 45 of the samples, the holes were fully filled with Biodentine® and in the other 45 samples, the holes were fully filled with MTA. The Biodentine® and the MTA samples were randomly divided into 3 subgroups of 15 specimens each: Group-1: MB composite; Group-2: SB composite; and Group-3: GIC. For the shear bond strength (SBS) test, each block was secured in a universal testing machine. Results: The highest (17.7±6.2 MPa) and the lowest (5.8±3.2 MPa) bond strength values were recorded for the MB composite-Biodentine® and the GIC-MTA, respectively. Although the MB composite showed significantly higher bond strength to Biodentine (17.7±6.2) than it did to MTA (8.9±5.7) (p<0.001), the SB composite (SB and MTA=7.4±3.3; SB and Biodentine®=8.0±3,6) and GIC (GIC and MTA=5.8±3.2; GIC and Biodentine=6.7±2.6) showed similar bond strength performance with MTA compared with Biodentine (p=0.73 and p=0.38, respectively). Conclusions: The new pure tricalcium-based pulp capping, repair, and endodontic material showed higher shear bond scores compared to MTA when used with the MB composite.